Efficiency in Vietnamese banking: A meta-regression analysis approach - Tin H. Ho; Dat T. Nguyen; Ngo Thanh; Tu D. Q. Le (International Journal of Financial Studies, 2021)
This study explains the differences and variances in the efficiency scores of the Vietnamese banking sector retrieved from 27 studies published in refereed academic journals under the framework of meta-regression analysis. These scores are mainly based on frontier efficiency measurements, which essentially are Data Envelopment Analysis (DEA) and Stochastic Frontier Analysis (SFA) for Vietnamese banks over the period of 2007-2019. The meta-regression is estimated by using truncated regression to obtain bias-corrected scores. Our findings suggest that only the year of publication is positively correlated with efficiency, whilst the opposite is true for the data type, and sample size.
Keywords: C13; C80; D24; G21; L25; 330; efficiency; frontier models; meta-regression analysis; Vietnamese banking industry